2009
DOI: 10.1128/aem.01042-08
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Analysis of Genes Encoding Homologues of Reductive Dehalogenases in “ Dehalococcoides ” sp. Strain CBDB1 by Using Terminal Restriction Fragment Length Polymorphism and Quantitative PCR

Abstract: The transcription of reductive dehalogenase homologous (rdh) genes of "Dehalococcoides" sp. strain CBDB1 was investigated during the growth and reductive dechlorination of 1,2,3-and 1,2,4-trichlorobenzene (TCB). A method was developed to monitor the expression of all 32 rdhA genes present in the genome based on reverse transcription-PCR amplification with 13 degenerate primer pairs and terminal restriction fragment length polymorphism (t-RFLP) analysis. With this approach, the upregulation of the transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 46 publications
9
61
0
Order By: Relevance
“…5A). A similar response was observed during 1,2,3-TCB and 1,2,4-TCB dechlorination by strain CBDB1 (44). Throughout the experiment, cbrA transcript levels were found to be 3-to 50-fold higher than those at the start of the incubation.…”
Section: Vol 77 2011 "Dehalococcoides" Spp In Hcb Anaerobic Transfsupporting
confidence: 56%
See 4 more Smart Citations
“…5A). A similar response was observed during 1,2,3-TCB and 1,2,4-TCB dechlorination by strain CBDB1 (44). Throughout the experiment, cbrA transcript levels were found to be 3-to 50-fold higher than those at the start of the incubation.…”
Section: Vol 77 2011 "Dehalococcoides" Spp In Hcb Anaerobic Transfsupporting
confidence: 56%
“…in Flix river sediment possessed rdhA genes corresponding to those previously identified in the genome of strain CBDB1 (44). Analysis of 57 T-RFs in the sample taken in the third week of the experiment showed that the Flix sediment batches contained 19 of the 32 rdh genes from strain CBDB1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations